Causes of wolf depredation increase in Minnesota from 1979-1998 - Harper, Elizabeth K.; Paul, William J.; Mech, L. David (DigitalCommons@University of Nebraska - Lincoln, 2005)
Wolf (Canis lupus) depredations on livestock in Minnesota have been increasing over the last 20 years. A major explanation cited for this increase is wolf range expansion, but no studies have tested this explanation. Additional reasons could include 1) wolf colonization of new areas within long-existing wolf range, 2) learning by wolves in established range, and 3) increased wolf density. We did not assess increasing wolf density as a factor because estimated wolf density in Minnesota has not increased. To assess how each of the other factors might have affected depredations, we created and analyzed a database of Minnesota's 923 verified depredations at 435 farms. We graphed the numbers of verified depredations and the number of farms with verified depredations to assess temporal trends and used ArcView GIS software to assess spatial relationships of the depredations. All 3 factors tested (colonization, range expansion, and learning) seemed to have contributed to wolf depredation increase. However, the proportion of depredations occurring due to wolf range expansion increased from 20% in 1989 to 48% in 1998.